2015
DOI: 10.1007/s11427-015-4803-x
|View full text |Cite
|
Sign up to set email alerts
|

AtGGM2014, an Arabidopsis gene co-expression network for functional studies

Abstract: Gene co-expression networks provide an important tool for systems biology studies. Using microarray data from the ArrayExpress database, we constructed an Arabidopsis gene co-expression network, termed AtGGM2014, based on the graphical Gaussian model, which contains 102,644 co-expression gene pairs among 18,068 genes. The network was grouped into 622 gene co-expression modules. These modules function in diverse house-keeping, cell cycle, development, hormone response, metabolism, and stress response pathways. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…In another study, high-scoring regulatory proteins (such as transcription factors, kinases and phosphatases) were fused into a co-expression network, enhancing correct prediction of phenotypes of known stress regulators from 36% to 62% [67]. Co-expression datasets of A. thaliana were used to show that biotic stress responses and hormone treatments induced several network modules and that hormones modified a module related to defence regulation, while effector proteins from P. syringae repressed two other modules [68]. Within these modules, genes of unknown function potentially contribute to plant defence responses.…”
Section: Omics and Network Analyses To Define The Innate Immune Systementioning
confidence: 99%
“…In another study, high-scoring regulatory proteins (such as transcription factors, kinases and phosphatases) were fused into a co-expression network, enhancing correct prediction of phenotypes of known stress regulators from 36% to 62% [67]. Co-expression datasets of A. thaliana were used to show that biotic stress responses and hormone treatments induced several network modules and that hormones modified a module related to defence regulation, while effector proteins from P. syringae repressed two other modules [68]. Within these modules, genes of unknown function potentially contribute to plant defence responses.…”
Section: Omics and Network Analyses To Define The Innate Immune Systementioning
confidence: 99%
“…One such approach, Gaussian Graphical Modelling, is commonly used as it allows researchers to interrogate the direct association between two genes, independent of the effects of surrounding genes present in the dataset. A number of thorough Gaussian Graphical Modelling studies in the model plant species Arabidopsis thaliana (Arabidopsis) have demonstrated the statistical power of this technique, and generated GCNs of select pathways and on a genome-wide scale (Wille et al, 2004; Ma et al, 2007; Ma et al, 2015). Another useful step for analysing complex datasets encompassing a wide range of tissues, developmental stages and stresses, is the use of batch-effect removal approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The original design was able to calculate Pcor data among a few thousand genes only [ 16 ]. Previously, we developed a random sampling-based method to overcome this obstacle and constructed the first genome-wide GGM network for Arabidopsis, followed by an updated network model termed AtGGM2014 [ 7 , 17 ]. Compared to other networks, AtGGM2014 contained more genes and identified additional modules participating in a large variety of plant processes, like development, metabolism, response to stresses, and response to hormones [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we developed a random sampling-based method to overcome this obstacle and constructed the first genome-wide GGM network for Arabidopsis, followed by an updated network model termed AtGGM2014 [ 7 , 17 ]. Compared to other networks, AtGGM2014 contained more genes and identified additional modules participating in a large variety of plant processes, like development, metabolism, response to stresses, and response to hormones [ 7 ]. For example, among many informative gene modules, it included hormonal signaling modules for phytohormones like auxin, abscisic acid, jasmonic acid, gibberellins, cytokinins, ethylene, and salicylic acid, demonstrating the network’s potential to facilitate systems biology studies on Arabidopsis gene functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation